Exploring the potential role of genus Sophora in the management of osteoporosis: a phytochemical and biological review - Aly, Shaza H.; Elbadry, Abdullah M. M.; El-Shazly, Mohamed; Hwang, Tsong-Long (Frontiers in Natural Products, 2023)
Bone metabolism is characterized by an interplay between the deposition of bone matrix and mineralization and the resorption process. Osteoporosis is a form of systemic metabolic bone condition that causes bone density to decline and its microarchitecture to deteriorate, increasing the risk of fracture owing to fragility. The underlying cause of this clinical disease lies in the imbalance in bone remodeling, in which bone resorption by osteoclasts predominates over bone creation by osteoblasts. Natural remedies have long been used to cure and prevent osteoporosis. Genus Sophora of the Fabaceae family comprises about 69 species that showed many pharmacological effects, including bone health preservation. The activity of Sophora sp. in maintaining bone health was attributed to its antioxidant, regenerative, and anti-inflammatory qualities. In this review, we focused on the therapeutic properties of the extracts and isolated compounds from the genus Sophora in maintaining bone health, with special emphasis on the management of osteoporosis.